Numerical analysis failure prediction of CFRP stiffened panels in the context of optimal airframe structural performance - Giannopoulos, Ioannis K.; Bleoju, Nicolae A.; Tourlomousis, Ilias; Theotokoglou, Efstathios E. (Hellenic Society for Theoretical and Applied Mechanics, 2019)
This paper presents the effect of stiffener damage on Carbon Fibre Reinforced Composite (CFRP) stiffened panels subjected to compression, for various stiffener design configurations. Nonlinear finite element progressive damage numerical simulations were used for the analysis. The investigation targeted the percentage decrease of the panel compression strength between the pristine (undamaged) and damaged stiffened panel states. The three designed cases sought, were assuming stiffened panels of the same weight but of different stiffener design. The study aimed at displaying that for CFRP stiffened panels used in aircraft structures and designed to carry loads where material strength could be the driver for the maximum compression loading capacity and not the structure’s resistance to buckling, the stiffener geometry and material damage propagation are some of the major parameters for optimal stiffened panel design. In that regards and for cost saving from expensive testing surveys, nonlinear finite element analysis is a valuable tool for preliminary design studies and optimal design down-selection.
Keywords: Composite structures; stiffened panel; progressive damage analysis; failure prediction